(untitled) (UNED Research Journal, 2023)
Introduction: Freshwater fish can be negatively affected by human disturbances like infrastructure, dikes or canals, and extensive agriculture, which affect forest cover and promote sedimentation. Objetive: To evaluate the spatio-temporal composition of freshwater fish and its relationship with some physical-chemical water variables in three tropical rivers. Methods: I worked in the Grande de Térraba y Esquinas basins, Costa Rica, in three control sites and three sites with dike and channel influence. I sampled twice a month at the end of the rainy season (October-December, 2010) and the beginning of the dry season (January-March, 2011). I measured water quality variables and determined the type of environment or substrate, speed and altitude. Results: I captured 742 fish (24 species, 12 families). The most representative were Astyanax aeneus (44%), Poeciliopsis retropinna (14%), Dormitator latifrons (8%), Priapichthys panamensis (7%), Cryptotheros sajica (6%) and Brachyrhaphis roseni (4%). There were no statistically significant differences among sites. Conclusion: The fluctuations of environmental variables, and the trends in fish abundance, richness, and distribution, did not differ among control sites and anthropologically affected sites.